Maternal health after Ebola: unmet needs and barriers to healthcare in rural Sierra Leone. Issue 1 (7th November 2019) - Elston, James W T; Danis, Kostas; Gray, Nell; West, Kim; Lokuge, Kamalini; Black, Benjamin; Stringer, Beverley; Jimmisa, Augustine S; Biankoe, Aiah; Sanko, Mohammed O; Kazungu, Donald S; Sang, Sibylle; et al.
Abstract: Sierra Leone has the world's highest estimated maternal mortality. Following the 2014–16 Ebola outbreak, we described health outcomes and health-seeking behaviour amongst pregnant women to inform health policy. In October 2016–January 2017, we conducted a sequential mixed-methods study in urban and rural areas of Tonkolili District comprising: household survey targeting women who had given birth since onset of the Ebola outbreak; structured interviews at rural sites investigating maternal deaths and reporting; and in-depth interviews (IDIs) targeting mothers, community leaders and health workers. We selected 30 clusters in each area: by random GPS points (urban) and by random village selection stratified by population size (rural). We collected data on health-seeking behaviours, barriers to healthcare, childbirth and outcomes using structured questionnaires. IDIs exploring topics identified through the survey were conducted with a purposive sample and analysed thematically. We surveyed 608 women and conducted 29 structured and 72 IDIs. Barriers, including costs of healthcare and physical inaccessibility of healthcare facilities, delayed or prevented 90% [95% confidence interval (CI): 80–95] (rural) vs 59% (95% CI: 48–68) (urban) pregnant women from receiving healthcare. Despite a general preference for biomedical care, 48% of rural and 31% of urban women gave birth outside of a health facility; of those, just 4% and 34%, respectively received skilled assistance. Women expressed mistrust of healthcare workers (HCWs) primarily due to payment demanded for 'free' healthcare. HCWs described lack of pay and poor conditions precluding provision of quality care. Twenty percent of women reported labour complications. Twenty-eight percent of villages had materials to record maternal deaths. Pregnant women faced important barriers to care, particularly in rural areas, leading to high preventable mortality and morbidity. Women wanted to access healthcare, but services available were often costly, unreachable and poor quality. We recommend urgent interventions, including health promotion, free healthcare access and strengthening rural services to address barriers to maternal healthcare.